Efficacy of dehydroepiandrosterone priming in women with poor ovarian response undergoing IVF/ICSI: a meta-analysis - Zhang, Jie; Jia, Hongyan; Diao, Feiyang; Ma, Xiang; Liu, Jiayin; Cui, Yugui (Frontiers in Endocrinology, 2023)
Background: Dehydroepiandrosterone (DHEA) may improve the outcomes of patients with poor ovarian response (POR) or diminished ovarian reserve (DOR) undergoing IVF/ICSI. However, the evidence remains inconsistent. This study aimed to investigate the efficacy of DHEA supplementation in patients with POR/DOR undergoing IVF/ICSI. Methods: PubMed, Web of Science, Cochrane Library, China National Knowledge Infrastructure (CNKI) were searched up to October 2022. Results: A total of 32 studies were retrieved, including 14 RCTs, 11 self-controlled studies and 7 case-controlled studies. In the subgroup analysis of only RCTs, DHEA treatment significantly increased the number of antral follicle count (AFC) (weighted mean difference : WMD 1.18, 95% confidence interval(CI): 0.17 to 2.19, P=0.022), while reduced the level of bFSH (WMD -1.99, 95% CI: -2.52 to -1.46, P<0.001), the need of gonadotropin (Gn) doses (WMD -382.29, 95% CI: -644.82 to -119.76, P=0.004), the days of stimulation (WMD -0.90, 95% CI: -1.34 to -0.47, P <0.001) and miscarriage rate (relative risk : RR 0.46, 95% CI: 0.29 to 0.73, P=0.001). The higher clinical pregnancy and live birth rates were found in the analysis of non-RCTs. However, there were no significant differences in the number of retrieved oocytes, the number of transferred embryos, and the clinical pregnancy and live birth rates in the subgroup analysis of only RCTs. Moreover, meta-regression analyses showed that women with lower basal FSH had more increase in serum FSH levels (b=-0.94, 95% CI: -1.62 to -0.25, P=0.014), and women with higher baseline AMH levels had more increase in serum AMH levels (b=-0.60, 95% CI: -1.15 to -0.06, P=0.035) after DHEA supplementation. In addition, the number of retrieved oocytes was higher in the studies on relatively younger women (b=-0.21, 95% CI: -0.39 to -0.03, P=0.023) and small sample sizes (b=-0.003, 95% CI: -0.006 to -0.0003, P=0.032). Conclusions: DHEA treatment didn’t significantly improve the live birth rate of women with DOR or POR undergoing IVF/ICSI in the subgroup analysis of only RCTs. The higher clinical pregnancy and live birth rates in those non-RCTs should be interpreted with caution because of potential bias. Further studies using more explicit criteria to subjects are needed.